Applying public participation GIS (PPGIS) to inform and manage visitor conflict along multi-use trails. Issue 3 (4th March 2018) - Wolf, Isabelle D.; Brown, Greg; Wohlfart, Teresa
ABSTRACT: Managing visitor conflict is an important task in protected areas. This study used public participation GIS (PPGIS) mapping and a visitor survey to research conflicts between mountain bikers and horse riders, and other groups frequenting trails for tourism and recreation in national parks in northern Sydney (Australia). The goal was to evaluate the effectiveness of the PPGIS for determining conflict locations, and to integrate stated reasons and conflict resolution measures in a model. The survey showed that 42% of mountain bikers and 69% of horse riders had experienced conflicts, with each other, motorbike riders, walkers/hikers and dog walkers. PPGIS effectively mapped concurrent usage intensity to predict potential conflict locations over a reasonably large study area thereby identifying trails of the greatest concern. PPGIS also offered high-quality GIS visualisation options, and the novelty of the PPGIS increased participant engagement. We evaluated PPGIS compared to questionnaire-based surveying, direct visitor observations, GPS tracking, traffic counters and cameras. Because visitor conflict occurs within a spatial context, conflict management will require greater spatial knowledge of visitor activity, which can be obtained through the innovative PPGIS mapping. A conflict model is presented that integrates this study's empirical findings on conflict reasons and resolutions with existing conflict theory.